Climate change adaptation with limited resources: adaptive capacity and action in small- and medium-sized municipalities - Dennis Fila; Hartmut Fünfgeld; Heindriken Dahlmann (Environment, Development and Sustainability, 2023)
Administrations in small- and medium-sized municipalities (SMM) are confronted with the impacts of climate change while having inadequate resources to adapt. In order to establish the current state of research on climate change adaptation in SMM, a systematic literature review was conducted. Using reported SMM adaptation in the peer-reviewed literature as our data base, we documented 115 adaptation initiatives between 2015 and 2021 matching our criteria, with substantial geographical and thematic differences. The qualitative analysis of highly relevant articles has shown that the specific understanding about the challenges and barriers of climate change adaptation in SMM remains limited. We highlight recent key trends and challenges and conclude by offering a refined research agenda for addressing identified knowledge gaps as well as key barriers in relation to SMM adaptation.
Keywords: 330; Climate change adaptation; Small-sized municipalities; Medium-sized municipalities; Barriers; Capacities; Government; Governance